Écrire sur l’Algérie. Les SHS à l’épreuve de la mobilisation citoyenne du 22 février 2019 - Karima Dirèche (L’Année du Maghreb)
This contribution is an opportunity to suggest a critical evaluation of the editorial adventure of the collective work L’Algérie au présent. Entre résistances et changements edited by IRMC-Karthala in May 2019. This work which focuses on Social sciences and humanities research in Algeria and about Algeria (in its contemporary dynamics) raises many questions about the conditions on knowledge production, theoretical and methodological training (and writing practices) and on the visibility of practices in SHS. This feedback will discuss the formal and implicit constraints on the development of research in a prevailing authoritarian environment.